DAMPAK KEBERADAAN AGROWISATA TERPADU GUNDALING FARMSTEAD PADA PEMBANGUNAN DI DESA LAU GUMBA KECAMATAN BERASTAGI KABUPATEN KARO SUMATERA UTARA - Gracia, Sarah; Sinaga, Roida Ervina; Sihaloho, Nani Kitti (JURNAL AGROTEKNOSAINS, 2023)
The aims of this research are (1) to see the extent of the development contribution provided by the existence of Gundaling Farmstead integrated agrotourism in Lau Gumba Village, (2) What is the impact of Gundaling Farmstead integrated agrotourism on the socio-economics of the surrounding community. The research steps begin with an initial identification process, then data collection (interviews and questionnaires), tabulation, data analysis, until finally producing conclusions and report suggestions. The community population in Jaranguda Hamlet, Lau Gumba Village, is 459 people based on the initial survey. Determination of the sample in this research was by using simple random sampling. For sampling, the Arikunto formula was used so that the sample taken was 45 people. The analytical method used is descriptive analysis and t-test statistical analysis. The results of this research show that there are real differences in social and economic conditions before and after the existence of the Gundaling Farmstead integrated agrotourism in Lau Gumba Village, Berastagi District, Karo Regency with the results of the t test. Social criteria: t table = 2.014 while t count = 31.737, then t count > t table, so H1 is accepted and H0 is rejected. Economic criteria: t table = 2.014 while t count = 23.991, then t count > t table, so H1 is accepted and H0 is rejected. The existence of the Gundaling Farmstead Integrated Agrotourism in Lau Gumba Village is proven by the results of hypothesis testing showing that there have been changes in social and economic conditions that are better than before the existence of this agrotourism.